(untitled) (CIPEEX, 2025)
Cancer is a group of diseases characterized by uncontrolled growth and proliferation of abnormal cells resulting from genetic and epigenetic changes. Nanotechnology has been increasingly explored in the field of cancer therapies due to its ability to improve the efficacy and reduce the side effects of drugs. The objective of this study is to compare the toxicity of lipid and polymeric delivery systems in cancer therapies that use nanotechnology. This is a literature review, and the BVS, PubMed, and Lilicas databases were used as the basis for the study. To perform the review, the following descriptors recognized by DeCS (Health Sciences Descriptors) were used, combined with the Boolean operators in the following sequence: “nanotechnology” and “cancer” and ‘treatment’ and “toxicity.” Articles published in the last five years in Portuguese and English were used as search filters. Fifty-five articles were found, of which 12 were excluded due to duplication. After screening titles and abstracts, 37 articles were excluded because, although they included the descriptors, they did not directly address the objective. Six articles that were compatible with the theme were selected. Based on the study of selected articles, lipid delivery systems (liposomes, micelles) favor the delivery of antitumor drugs by mimicking the cell membrane and controlled release, but their toxicity depends on the lipid composition and production method, and they can induce immune responses (inflammation, anaphylaxis) and accumulate in the liver and spleen, limiting the safety of this method. Polymeric nanoparticles, on the other hand, have greater biological stability and allow for controlled release (including by stimuli), with lower relative immunogenicity; however, the biodegradability of the polymer and its degradation products can be cytotoxic, associated with hepatotoxicity, nephrotoxicity, and neuropathy depending on the formulation, size, and biodistribution. Therefore, standardized toxicological evaluations (in vitro/in vivo), detailed characterization (size, surface area, biodegradability), pharmacokinetic studies, and preclinical and clinically relevant models are essential to mitigate risks and guide platform selection according to the profile of the drug, tumor, and patient.